Anxiety Levels and Emesis Gravidarum Severity in Pregnant Women: Tingkat Kecemasan dan Derajat Keparahan Mual Hamil pada Wanita Hamil - Putri, Arizki Amalia; Cholifah , Siti; Widowati, Hesty; Rinata, Evi (Universitas Muhammadiyah Sidoarjo, 2025)
Abstract — General Background: Emesis gravidarum is one of the most common early pregnancy symptoms, influenced by hormonal, psychosocial, nutritional, and maternal factors. Specific Background: Psychological distress, particularly anxiety, is believed to exacerbate nausea and vomiting during pregnancy, but evidence in the Indonesian context remains limited. Knowledge Gap: Previous studies have not sufficiently explored the association between maternal anxiety and the severity of emesis gravidarum in first-trimester pregnancies using validated tools. Aims: This study aimed to examine the relationship between maternal anxiety levels and the severity of emesis gravidarum. Results: An analytic survey with a cross-sectional design was conducted among 30 first-trimester pregnant women selected by quota sampling. Data were collected using the Depression Anxiety Stress Scale (DASS) and PUQE-24 questionnaire. Fisher’s Exact Test revealed a significant association (p = 0.006 < α = 0.05) between maternal anxiety levels and emesis gravidarum severity. Novelty: This study provides empirical evidence on the role of psychological status, particularly anxiety, in influencing emesis gravidarum symptoms among Indonesian primigravida. Implications: The findings suggest the importance of early screening and anxiety management interventions by healthcare providers to prevent worsening conditions such as hyperemesis gravidarum. Highlights: Anxiety severity is significantly linked to emesis gravidarum levels. Primigravida mothers are more vulnerable to moderate nausea and vomiting. Early anxiety management may reduce the risk of hyperemesis gravidarum. Keywords: Emesis Gravidarum, Anxiety, DASS, PUQE-24, Pregnancy